Acid-rain-resistant protective nano-coating for red sandstone dam body of water conservancy project reservoir and preparation method thereof

By combining nanotitanium oxide and nanographene oxide with silicone resin, hydroxyacrylic resin containing carbon-carbon bonds and silicon-oxygen bonds was prepared, and the existing acid rain-resistant coatings were solved in the protection of red sandstone dams in the acid rain area reservoirs. The problems of insufficient acid resistance and other problems have achieved multiple performance improvements in the paint.

CN119463598APending Publication Date: 2025-02-18NANJING HYDRAULIC RES INST +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411654177.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing acid rain-resistant coatings have problems such as insufficient acid resistance, opacity, water resistance and durability in the protection of red sandstone dams in the reservoir in the acid rain area, which is difficult to meet the multiple performance requirements of red sandstone dams in the reservoir.

Method used

Nanotitanium oxide and nanographene oxide were combined with silicone resin containing silicone bonds to prepare hydroxyacrylic resin containing carbon-carbon bonds as the main film-forming resin for the coating to form an aqueous nanocoating.

Benefits of technology

The coating has extremely strong acid resistance, colorless and transparent, good water resistance and durability, and has good bonding strength to the rock mass, which can maintain performance for a long time under simulated acid rain conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005141736440000081
    Figure BDA0005141736440000081
  • Figure BDA0005141736440000082
    Figure BDA0005141736440000082
  • Figure BDA0005141736440000091
    Figure BDA0005141736440000091
Patent Text Reader

Abstract

The invention discloses a water conservancy project reservoir red sandstone dam body acid rain resistant protection nano coating and a preparation method thereof. The coating is formed by mixing a component A and a component B according to the mass ratio of (3-8): 1, wherein the component A is prepared from the following substances in parts by mass: 50 to 70 parts of water-based hydroxy acrylic resin, 10 to 30 parts of water-based organic silicon resin, 0.4 to 0.6 part of nano titanium oxide, 0.6 to 0.8 part of nano graphene oxide, 10 to 15 parts of deionized water, 4 to 6 parts of a coalescing agent, 0.1 to 0.3 part of a catalyst, 0.1 to 0.2 part of a de-foaming agent and 0.4 to 0.6 part of a dispersing agent; the component B is prepared from the following substances in parts by mass: 80 to 90 parts of hexamethylene diisocyanate tripolymer, 5 to 10 parts of propylene glycol monomethyl ether acetate and 5 to 10 parts of dipropylene glycol methyl ether acetate. The nano coating disclosed by the invention has extremely strong acid resistance; colorless and transparent; the water resistance is good; the durability is good; and good bonding strength with rock mass is achieved. The method is especially suitable for acid rain protection of a red sandstone dam body of a water conservancy project reservoir.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nano coatings, and in particular to an acid rain resistant protective nano coating for a red sandstone dam body of a water conservancy project reservoir and a preparation method thereof. Background Art

[0002] Red sandstone is widely distributed in southwest and central-south my country. This type of sedimentary rock appears red because the colloids contain iron compounds. Many reservoirs in water conservancy projects are made from the abundant local red sandstone resources, and the dam bodies of the reservoirs are built with red sandstone.

[0003] Acid rain refers to atmospheric precipitation with a pH value of less than 5.6, and its forms mainly include liquid precipitation, solid precipitation, and mixed precipitation (rain, snow, hail, etc.). my country is one of the three major acid rain areas in the world, and most of them are sulfuric acid and nitric acid types. In 2021, the area of ​​acid rain areas in China was 369,000 m 2 , accounting for 3.8% of the country's land area. The most serious areas are South China and Central China, followed by Southwest China. The Sichuan Basin is located in the center of the Southwest region. The special geographical, climatic conditions and industrial economic distribution also lead to frequent acid rain pollution in some areas.

[0004] The chemical composition of red sandstone contains metal oxides such as CaO, AI2O3, K2O, Fe2O3, and Na2O. Under the influence of acid rain, chemical reactions easily occur to generate soluble salts and carbon dioxide gas. Long-term corrosion by acid rain will affect the structure of the red sandstone dam and endanger the safety of the reservoir. All parties are actively seeking acid rain-resistant protection measures for the red sandstone dam of reservoirs in water conservancy projects in areas with severe acid rain.

[0005] Due to the special conditions of the red sandstone dam reservoir, several acid rain resistant coatings currently available on the market are not applicable. The materials used for the reservoir must first be water-based, non-toxic and pollution-free. All solvent-based materials are not applicable. The red sandstone dam is generally required to maintain its original appearance, so the materials used are required to be colorless and transparent. The dam is often in water, so the materials should have good water resistance. Single-component materials are basically not suitable. Part of the dam is also exposed to the sun, so the materials should also have good durability. In summary, the coating used for acid rain protection of the red sandstone dam of the water conservancy project reservoir should have the following performance characteristics: (1) extremely strong acid resistance; (2) colorless and transparent; (3) good water resistance; (4) good durability; (5) good bonding strength with the rock mass.

[0006] CN109294382A discloses a super weather-resistant, acid-rain-resistant, and sewage-resistant inorganic nano-ceramic coating and its preparation method, which has good weather-resistant and acid-resistant properties. It is a single-component silicone-acrylic emulsion coating, and its water resistance and bonding strength with the substrate cannot meet the protection requirements of the red sandstone dam of the reservoir. In addition, the acid resistance is not strong enough. CN116751499A discloses a nano-silicon nitride-modified high-temperature solvent-free epoxy wear-resistant and acid-resistant coating. The coating uses nano-silicon nitride and nano-silicon oxide modified epoxy resin as the main film-forming resin, and has good wear resistance and certain acid resistance. However, the coating belongs to an organic solvent-based coating and is difficult to make into a transparent coating. In addition, the acid resistance of the epoxy group and ether bond in the epoxy resin is insufficient compared with the carbon-carbon bond and the silicon-oxygen bond. Therefore, the coating is not suitable for the acid rain protection of the red sandstone dam of the reservoir in the acid rain area. CN105505086A discloses an acid rain resistant and dustproof topcoat and its preparation method, which belongs to a single-component silicone resin coating. The acid rain resistance is that there is no abnormality after being immersed in acid rain solution for 48 hours. The acid resistance is not enough to be used for the protection of red sandstone in acid rain areas, and the bonding strength and water resistance are not enough. CN115491061A discloses a nano-coating for weathering and corrosion protection of red sandstone in water conservancy projects and its preparation method. The coating has extremely excellent weathering resistance and has a good effect on the weathering protection of red sandstone in non-acid rain areas. However, in areas with severe acid rain, especially when ultraviolet radiation is superimposed on acid rain, the acid rain resistance is insufficient. Indoor tests show that when the temperature rises, its acid resistance decreases significantly. Summary of the invention

[0007] The invention provides a nano coating for acid rain resistance protection of red sandstone dam bodies of water conservancy project reservoirs. In the coating, hydroxy acrylic resin containing carbon-carbon bonds obtained by composite modification of nano titanium oxide and nano graphene oxide with organic silicon resin containing silicon-oxygen bonds is selected as the main film-forming resin of the coating. The nano titanium oxide and nano graphene oxide have good acid resistance and are easy to obtain.

[0008] The technical solution adopted by the present invention is as follows:

[0009] A nano coating for acid rain resistant protection of red sandstone dams in water conservancy projects, wherein the coating is mixed with component A and component B in a mass ratio of component A: component B = 3-8:1, wherein

[0010] Component A consists of the following substances in parts by mass:

[0011] 50-70 parts of water-based hydroxy acrylic resin, 10-30 parts of water-based silicone resin, 0.4-0.6 parts of nano titanium oxide, 0.6-0.8 parts of nano graphene oxide, 10-15 parts of deionized water, 4-6 parts of film-forming aid, 0.1-0.3 parts of catalyst, 0.1-0.2 parts of defoaming agent, 0.4-0.6 parts of dispersant;

[0012] Component B is composed of the following substances in parts by mass:

[0013] 80-90 parts of hexamethylene diisocyanate trimer, 5-10 parts of propylene glycol monomethyl ether acetate, and 5-10 parts of dipropylene glycol methyl ether acetate.

[0014] The film-forming aid is at least one of ethylene glycol butyl ether and diethylene glycol butyl ether.

[0015] The catalyst is tetraisopropyl titanate.

[0016] The defoaming agent is dimethyl silicone oil; the dispersant is a silane coupling agent.

[0017] The coating is prepared by mixing component A and component B in a mass ratio of component A: component B = 4:1, wherein component A is composed of the following substances in parts by mass:

[0018] Water-based hydroxy acrylic resin 60%, water-based silicone resin 20%, nano titanium oxide 0.5%, nano graphene oxide 0.7%, deionized water 13%, film-forming aid 5%, catalyst 0.2%, defoamer 0.1%, dispersant 0.5%;

[0019] Component B is composed of the following substances in parts by mass:

[0020] Hexamethylene diisocyanate trimer 85%, propylene glycol monomethyl ether acetate 7%, dipropylene glycol methyl ether acetate 8%.

[0021] The coating is used in acid rain resistant protection of red sandstone dam bodies in water conservancy project reservoirs and can be applied by brushing, rolling or spraying.

[0022] The method for preparing the acid rain resistant protective nano coating for the red sandstone dam of a water conservancy project reservoir comprises the following steps:

[0023] S1: Add the formulated amount of hydroxy acrylic resin and silicone resin into a reaction kettle, raise the temperature to 90-95° C., drop the catalyst, keep the temperature for reaction for 1-4 hours after the drop is complete, cool and discharge the material for standby use, and obtain a composite resin;

[0024] S2: Add deionized water, dispersant and nanoparticles to a high-speed disperser, remove after high-speed dispersion, ultrasonically cavitate in an ultrasonic cavitation instrument for 10 to 20 minutes, remove for standby use, add the composite resin prepared in the first step, the nanoparticle system that has been ultrasonically cavitated, the film-forming aid and the defoaming agent to a high-speed disperser, disperse at a speed of 4000 to 5000 rpm for 20 to 40 minutes, and obtain a finished product component A.

[0025] S3: Add three raw materials of component B into a high-speed disperser, and disperse for 20 to 40 minutes at a speed of 4000 to 5000 rpm to obtain a finished product component B;

[0026] S4: When using, mix component A and component B evenly according to the proportion.

[0027] In step S1, the catalyst is dripped completely within 1 to 1.5 hours.

[0028] In step S2, the dispersion is performed at a rotation speed of 5000 to 6000 rpm for 10 to 30 minutes.

[0029] In the present invention, nanoparticles are uniformly dispersed in the resin matrix in a suitable manner, which can significantly improve the comprehensive performance of the paint film; the best acid resistance among chemical bonds is carbon-carbon bond and silicon-oxygen bond, the thermal stability of a single carbon-carbon bond is not very good, resulting in a significant decrease in performance when long-term ultraviolet irradiation is superimposed on acid rain, and the silicon-oxygen bond has a large bond energy and has good thermal stability and acid resistance, but poor water resistance. In the present invention, under the action of a catalyst, hydroxy acrylic resin and silicone resin undergo a condensation reaction, and the molecular chain contains both carbon-carbon bonds and silicon-oxygen bonds, rather than a simple physical mixture, so that the two can be organically compounded to make up for their respective deficiencies; at the same time, nanoparticles have surface and interface effects and quantum size effects. The present invention selects nano titanium oxide and nano graphene oxide to be compositely modified with silicone resin containing silicon-oxygen bonds to obtain a hydroxy acrylic resin containing carbon-carbon bonds as the main film-forming resin of the coating, which can significantly improve the comprehensive performance of the paint film, especially acid resistance.

[0030] Beneficial effects:

[0031] The nano coating of the present invention has strong acid resistance, colorless and transparent, good water resistance, good durability, and good bonding strength with the rock mass. It is especially suitable for acid rain protection of red sandstone dams in water conservancy projects and reservoirs, with a bonding strength of ≥2.0Mpa with the red sandstone matrix, no bubbling or peeling for 30 days under 30% sulfuric acid at 50°C, and no bubbling or peeling for 360 days under simulated acid rain conditions. DETAILED DESCRIPTION

[0032] Example 1

[0033] The formula of the acid rain resistant protective nano coating for the red sandstone dam of the water conservancy project reservoir is as follows:

[0034] It is divided into component A and component B, and component B is the curing system.

[0035] A component formula: The components and their mass fractions (%) are as follows:

[0036] Water-based hydroxy acrylic resin 60%, water-based silicone resin 20%, nano titanium oxide 0.5%, nano graphene oxide 0.7%, deionized water 13%, film-forming aid ethylene glycol butyl ether 5%, catalyst tetraisopropyl titanate 0.2%, defoamer dimethyl silicone oil 0.1%, dispersant silane coupling agent KH560 0.5%;

[0037] The components of component B and their mass fractions are as follows:

[0038] 85 parts of hexamethylene diisocyanate trimer, propylene glycol monomethyl ether acetate (C6H 12 O3) 7 parts, dipropylene glycol methyl ether acetate (C9H 18 (24) 8 parts;

[0039] The raw materials of components A and B above are all commercially available raw materials; water-based hydroxy acrylic resin was purchased from Wanhua Chemical, model: 2042N), and water-based silicone resin was purchased from Wacker, model: SILRESMP 50E

[0040] The preparation method is divided into three steps:

[0041] Step 1: Add the formulated amount of hydroxy acrylic resin and water-based silicone resin into the reaction kettle, heat it to 95°C, add the catalyst dropwise, and complete the addition within 1.5 hours. After the addition is completed, keep the temperature for reaction for 2 hours, cool and discharge the material for standby use to obtain a composite resin.

[0042] Step 2: Add deionized water, dispersant and nanoparticles to a high-speed disperser, disperse at 6000 rpm for 10 minutes, remove, ultrasonically cavitate in an ultrasonic cavitation instrument for 20 minutes, remove for standby use, add the composite resin prepared in the first step, the ultrasonically cavitated nanoparticle system, film-forming aid and defoaming agent to a high-speed disperser, disperse at 5000 rpm for 20 minutes to obtain a finished product component A.

[0043] Step 3: Add the three raw materials of component B into a high-speed disperser and disperse them for 20 minutes at a speed of 5000 rpm to obtain the finished product component B.

[0044] When using, mix component A and component B in a mass ratio of component A: component B = 4:1. It can be applied by brushing, rolling or spraying. Component A and component B must be used up within 30 minutes after mixing.

[0045] Example 2

[0046] The formula of the acid rain resistant protective nano coating for the red sandstone dam of the water conservancy project reservoir is as follows:

[0047] Component A consists of the following substances in parts by mass:

[0048] 50 parts of water-based hydroxy acrylic resin, 10 parts of water-based silicone resin, 0.4 parts of nano titanium oxide, 0.6 parts of nano graphene oxide, 10 parts of deionized water, 4 parts of film-forming aid diethylene glycol butyl ether, 0.1 parts of catalyst tetraisopropyl titanate, 0.1 parts of defoaming agent dimethyl silicone oil, 0.4 parts of dispersant silane coupling agent KH560;

[0049] Component B is composed of the following substances in parts by mass:

[0050] 80 parts of hexamethylene diisocyanate trimer, 10 parts of propylene glycol monomethyl ether acetate, and 10 parts of dipropylene glycol methyl ether acetate.

[0051] The above raw materials of components A and B are all commonly used raw materials on the market;

[0052] The preparation method is divided into three steps:

[0053] Step 1: Add the formulated amount of hydroxy acrylic resin and water-based silicone resin into the reaction kettle, heat it to 90°C, add the catalyst dropwise, and complete the addition within 1.5 hours. After the addition is completed, keep the temperature for reaction for 2 hours, cool and discharge the material for standby use to obtain a composite resin.

[0054] Step 2: Add deionized water, dispersant and nanoparticles to a high-speed disperser, disperse at a speed of 5000 rpm for 30 minutes, remove, ultrasonically cavitate in an ultrasonic cavitation instrument for 10 minutes, remove for standby use, add the composite resin prepared in the first step, the ultrasonically cavitated nanoparticle system, film-forming aid and defoaming agent to a high-speed disperser, disperse at a speed of 4000 rpm for 40 minutes, and obtain a finished product component A.

[0055] Step 3: Add the three raw materials of component B into a high-speed disperser and disperse them at a speed of 4000 rpm for 40 minutes to obtain the finished product component B.

[0056] When using, mix component A and component B in a mass ratio of component A: component B = 4:1. It can be applied by brushing, rolling or spraying. Component A and component B must be used up within 30 minutes after mixing.

[0057] Example 3

[0058] The formula of the acid rain resistant protective nano coating for the red sandstone dam of the water conservancy project reservoir is as follows:

[0059] Component A consists of the following substances in parts by mass:

[0060] 70 parts of water-based hydroxy acrylic resin, 30 parts of water-based silicone resin, 0.6 parts of nano titanium oxide, 0.8 parts of nano graphene oxide, 15 parts of deionized water, 6 parts of film-forming aid diethylene glycol butyl ether, 0.3 parts of catalyst tetraisopropyl titanate, 0.2 parts of defoaming agent dimethyl silicone oil, 0.6 parts of dispersant silane coupling agent KH560;

[0061] Component B is composed of the following substances in parts by mass:

[0062] 90 parts of hexamethylene diisocyanate trimer, 5 parts of propylene glycol monomethyl ether acetate, and 5 parts of dipropylene glycol methyl ether acetate.

[0063] The above raw materials of components A and B are all commonly used raw materials on the market;

[0064] The preparation method is divided into three steps:

[0065] Step 1: Add the formulated amount of hydroxy acrylic resin and water-based silicone resin into the reaction kettle, heat it to 90°C, add the catalyst dropwise, and complete the addition within 1.5 hours. After the addition is completed, keep the temperature for reaction for 2 hours, cool and discharge the material for standby use to obtain a composite resin.

[0066] Step 2: Add deionized water, dispersant and nanoparticles to a high-speed disperser, disperse at a speed of 5000 rpm for 30 minutes, remove, ultrasonically cavitate in an ultrasonic cavitation instrument for 10 minutes, remove for standby use, add the composite resin prepared in the first step, the ultrasonically cavitated nanoparticle system, film-forming aid and defoaming agent to a high-speed disperser, disperse at a speed of 4000 rpm for 40 minutes, and obtain a finished product component A.

[0067] Step 3: Add the three raw materials of component B into a high-speed disperser and disperse them at a speed of 4000 rpm for 40 minutes to obtain the finished product component B.

[0068] When using, mix component A and component B in a mass ratio of component A: component B = 6:1. It can be applied by brushing, rolling or spraying. Component A and component B must be used up within 30 minutes after mixing.

[0069] Comparative Example 1

[0070] The formula of the acid rain resistant protective nano coating for the red sandstone dam of the water conservancy project reservoir is as follows:

[0071] It is divided into component A and component B, and component B is the curing system.

[0072] A component formula: The components and their mass fractions (%) are as follows:

[0073] 80 parts of water-based hydroxy acrylic resin, 0 parts of water-based silicone resin, 0.5 parts of nano titanium oxide, 0.7 parts of nano graphene oxide, 13.2 parts of deionized water, 5 parts of film-forming aid ethylene glycol butyl ether, 0 parts of catalyst tetraisopropyl titanate, 0.1 parts of defoaming agent dimethyl silicone oil, 0.5 parts of dispersant silane coupling agent KH560;

[0074] The components of component B and their mass fractions are as follows:

[0075] 85 parts of hexamethylene diisocyanate trimer, propylene glycol monomethyl ether acetate (C6H 12 O3) 7 parts, dipropylene glycol methyl ether acetate (C9H 18 (24) 8 parts;

[0076] The raw materials of components A and B above are all commercially available raw materials; water-based hydroxy acrylic resin, Wanhua Chemical 2042N. No silicone resin was added in this control example, so the preparation method was carried out in two steps:

[0077] Step 1: Add deionized water, dispersant, and nanoparticles to a high-speed disperser, disperse at 6000 rpm for 10 minutes, remove, ultrasonically cavitate in an ultrasonic cavitation instrument for 20 minutes, remove for standby use, add the ultrasonically cavitated nanoparticle system, film-forming aid, and defoaming agent to a high-speed disperser, disperse at 5000 rpm for 20 minutes, and obtain a finished product component A.

[0078] Step 2: Add the three raw materials of component B into a high-speed disperser and disperse them for 20 minutes at a speed of 5000 rpm to obtain the finished product component B.

[0079] When using, mix component A and component B in a mass ratio of component A: component B = 4:1. It can be applied by brushing, rolling or spraying. Component A and component B must be used up within 30 minutes after mixing.

[0080] Comparative Example 2

[0081] The formula of the acid rain resistant protective nano coating for the red sandstone dam of the water conservancy project reservoir is as follows:

[0082] It is divided into component A and component B, and component B is the curing system.

[0083] A component formula: The components and their mass fractions (%) are as follows:

[0084] 60 parts of water-based hydroxy acrylic resin, 20 parts of water-based silicone resin, 0 parts of nano titanium oxide, 0 parts of nano graphene oxide, 14.7 parts of deionized water, 5 parts of film-forming aid ethylene glycol butyl ether, 0.2 parts of catalyst tetraisopropyl titanate, 0.1 parts of defoaming agent dimethyl silicone oil, 0 parts of dispersant silane coupling agent KH560;

[0085] The components of component B and their mass fractions are as follows:

[0086] 85 parts of hexamethylene diisocyanate trimer, propylene glycol monomethyl ether acetate (C6H 12 O3) 7 parts, dipropylene glycol methyl ether acetate (C9H 18 (24) 8 parts;

[0087] The raw materials of components A and B above are all commercially available raw materials; water-based hydroxy acrylic resin, manufacturer: Wanhua Chemical, model: 2042N, water-based silicone resin, manufacturer: Wacker, model: SILRESMP 50E.

[0088] The preparation method is divided into three steps:

[0089] Step 1: Add the formulated amount of hydroxy acrylic resin and water-based silicone resin into the reaction kettle, heat it to 95°C, add the catalyst dropwise, and complete the addition within 1.5 hours. After the addition is completed, keep the temperature for reaction for 2 hours, cool and discharge the material for standby use to obtain a composite resin.

[0090] Step 2: Add deionized water, the composite resin prepared in the first step, a film-forming aid, and a defoaming agent into a high-speed disperser, and disperse for 20 minutes at a speed of 5000 rpm to obtain a finished product component A.

[0091] Step 3: Add the three raw materials of component B into a high-speed disperser and disperse them for 20 minutes at a speed of 5000 rpm to obtain the finished product component B.

[0092] When using, mix component A and component B in a mass ratio of 4:1. It can be applied by brushing, rolling or spraying. Component A and component B must be used up within 30 minutes after mixing. Main performance indicators:

[0093] The main performance indicators of the acid rain resistant protective nano coating for red sandstone dam of a water conservancy project reservoir prepared in Example 1 are shown in Table 1.

[0094] Table 1

[0095]

[0096] The concentrations of various ions in the homemade simulated acid rain are shown in Table 2.

[0097] Table 2

[0098]

[0099] Hydroxy acrylic resin contains carbon-carbon bonds, and silicone resin contains silicon-oxygen bonds. However, the thermal stability of a single carbon-carbon bond is insufficient, and the acid resistance will be reduced under high temperature environment. The silicon-oxygen bond has a large bond energy, and has good thermal stability when having good acid resistance, but insufficient water resistance. In the present invention, under the action of a catalyst, the hydroxy acrylic resin and the water-based silicone resin undergo a condensation reaction, and the molecular chain contains both carbon-carbon bonds and silicon-oxygen bonds, rather than a simple physical mixture, so that the two can be organically composited to make up for their respective deficiencies and bring the comprehensive properties such as acid rain resistance to the best. In addition, nano titanium oxide and nano graphene oxide have good acid resistance in addition to the small size effect of nanoparticles. The composite resin formed by the hydroxy acrylic resin and the water-based silicone resin is further improved by these two nanoparticles, and the prepared coating has excellent comprehensive properties such as acid rain resistance, and can be applied to the acid rain protection of the red sandstone dam body of the reservoir of a water conservancy project.

[0100] Compared with control examples 1 and 2, the performance is significantly improved. The test method and results are shown in Table 3.

[0101] Table 3

[0102]

Claims

1. A nano coating for acid rain protection of red sandstone dams in water conservancy projects, characterized in that: The coating is prepared by mixing component A and component B in a mass ratio of 3 to 8:1, wherein component A is composed of the following substances in parts by mass: 50-70 parts of water-based hydroxy acrylic resin, 10-30 parts of water-based silicone resin, 0.4-0.6 parts of nano titanium oxide, 0.6-0.8 parts of nano graphene oxide, 10-15 parts of deionized water, 4-6 parts of film-forming aid, 0.1-0.3 parts of catalyst, 0.1-0.2 parts of defoaming agent, 0.4-0.6 parts of dispersant; Component B is composed of the following substances in parts by mass: 80-90 parts of hexamethylene diisocyanate trimer, 5-10 parts of propylene glycol monomethyl ether acetate, and 5-10 parts of dipropylene glycol methyl ether acetate.

2. The acid rain resistant protective nano coating for red sandstone dam of a water conservancy project reservoir according to claim 1 is characterized in that: The film-forming aid is at least one of ethylene glycol butyl ether and diethylene glycol butyl ether.

3. The acid rain resistant protective nano coating for red sandstone dam of a water conservancy project reservoir according to claim 1 is characterized in that: The catalyst is tetraisopropyl titanate.

4. The acid rain resistant protective nano coating for red sandstone dam of a water conservancy project reservoir according to claim 1, characterized in that: The defoaming agent is dimethyl silicone oil.

5. The acid rain resistant protective nano coating for red sandstone dam of a water conservancy project reservoir according to claim 1, characterized in that: The dispersant is a silane coupling agent.

6. The acid rain resistant protective nano coating for red sandstone dam of a water conservancy project reservoir according to claim 1, characterized in that: The coating is prepared by mixing component A and component B in a ratio of 4:1, wherein component A is composed of the following substances in parts by weight: 60 parts of water-based hydroxy acrylic resin, 20 parts of water-based silicone resin, 0.5 parts of nano titanium oxide, 0.7 parts of nano graphene oxide, 13 parts of deionized water, 5 parts of film-forming aid, 0.2 parts of catalyst, 0.1 parts of defoaming agent, and 0.5 parts of dispersant; Component B is composed of the following substances in parts by mass: 85 parts of hexamethylene diisocyanate trimer, 7 parts of propylene glycol monomethyl ether acetate, and 8 parts of dipropylene glycol methyl ether acetate.

7. The method for preparing the acid rain resistant protective nano coating for red sandstone dam of a water conservancy project reservoir according to any one of claims 1 to 6, characterized in that: The steps include: S1: Add the formulated amount of hydroxy acrylic resin and water-based silicone resin into a reaction kettle, raise the temperature to 90-95° C., drop the catalyst, keep the temperature for 1-4 hours after the drop is complete, cool and discharge the material for standby use, and obtain a composite resin; S2: adding deionized water, dispersant, and nanoparticles to a high-speed disperser, removing the mixture after high-speed dispersion, ultrasonically cavitating the mixture in an ultrasonic cavitation instrument for 10 to 20 minutes, removing the mixture for standby use, adding the composite resin prepared in the first step, the nanoparticle system that has been ultrasonically cavitated, a film-forming aid, and a defoaming agent to a high-speed disperser, and dispersing the mixture at a speed of 4000 to 5000 rpm for 20 to 40 minutes to obtain a finished product component A; S3: Add the three raw materials of component B into a high-speed disperser and disperse them at a speed of 4000 to 5000 rpm for 20 to 40 minutes to obtain a finished component B; S4: When using, mix component A and component B evenly according to the proportion.

8. The method for preparing the acid rain resistant protective nano coating for red sandstone dam of a water conservancy project reservoir according to claim 7, characterized in that: In step S1, the catalyst is dripped in 1 to 1.5 hours.

9. The method for preparing the acid rain resistant protective nano coating for red sandstone dam of a water conservancy project reservoir according to claim 7, characterized in that: In step S2, the dispersion is carried out at a rotation speed of 5000 to 6000 rpm for 10 to 30 minutes.

10. Use of the coating according to any one of claims 1 to 6 in acid rain protection of red sandstone dam bodies in water conservancy project reservoirs.

Citation Information

Patent Citations

  • Acid-rain-resistant dustproof finish-coat paint and preparation method thereof

    CN105505086A

  • Super weather-resistant acid rain-resistant anti-contamination aqueous inorganic nano ceramic coating and preparation method thereof

    CN109294382A

  • Nano silicon nitride modified high-temperature-resistant solvent-free epoxy wear-resistant acid-resistant coating

    CN116751499A

  • Water conservancy project red sandstone anti-weathering and anti-corrosion protection nano coating and preparation method thereof

    CN115491061A